Staphylococcus aureus resistance to non-β-lactam antibiotics: global genomic epidemiology and machine learning feasibility assessment - Saeid Sadeghi Ghazi Chaki; Maryam Abdulrahman Najim; Lina A. Hassan; Saleh A. S. AlAbdulhadi; Zahraa Abbas Al-Khafaji; M. K. Sharma; Ahmed Shihab Ahmed; Ali Batool Ahmed; Malik Bader Alazzam; Mohammad Sholeh (Molecular Genetics and Genomics, 2026)

Exogenous hesperidin orchestrates antioxidant defense, osmolyte metabolism, and nutrient homeostasis to mitigate heavy metal toxicity in canola - Sherjeel Hashmat; Humaira Yasmeen; Bakhrom Jobborov; Muhammad Imran; Mohammed S. Alotaibi; Hossam S. El-Beltagi; Usman Zulfiqar; Amna Batool; Umer Farooq (BioMetals, 2026)

A review on polymeric and nanocomposite materials for heavy metal removal from water: bibliometric analysis - M. N. Haider; M. Naveed; A. Shah; A. Arjunan; L. S. Jasim; T. B. Tariq; M. A. Zawar; T. Javed; K. Saadallah; M. Batool (International Journal of Energy and Water Resources, 2026)

Is grip strength a marker for cognitive function, neurodegeneration, and resilience? - Alexander Ivan B. Posis; Hilary L. Colbeth; Mihika S. Deshpande; Kristen M. George; Batool Rizvi; Rifat B. Alam; Ruijia Chen; Dan M. Mungas; Paola Gilsanz; María M. Corrada; Rachel A. Whitmer (GeroScience, 2025)
Assessing whether grip strength is associated with cognitive decline and brain health could help identify a target to prevent or delay cognitive impairment. Therefore, we tested whether grip strength is associated with brain health as indicated by magnetic resonance imaging and domain specific cognitive decline. We also assessed whether grip strength was a cognitive resilience proxy using moderation tests. This study included cognitive and neuroimaging data from 861 participants in three harmonized cohorts. We fit multivariable linear mixed-effects and linear regression models to test associations between grip strength, neuroimaging markers, and cognition. We also tested moderation by gender and age. Greater grip strength was associated with slower verbal episodic memory decline and greater total gray matter volume. Associations of grip strength with executive function, total hippocampal volume, and white matter hyperintensities were not significant, but in the expected direction. Age moderated associations of grip strength and white matter hyperintensities. Grip strength was a significant proxy for cognitive resilience related to white matter hyperintensity volume and verbal episodic memory decline only. Future research should examine other measures of physical performance that are associated with later-life cognitive and brain health.

Ameliorating textile effluent phytotoxicity in Vigna radiate through biosynthesized Fe/Zn bimetallic nanoparticles: sustainable approach for environmental remediation - F. Batool; F. Mahmood; T. Shahzad; S. Hussain (International Journal of Environmental Science and Technology, 2025)

Removal of chromium from electroplating wastewater using chitosan-coconut shell composite: kinetics, thermodynamics and artificial neural networks modeling - F. Batool; T A Kurniawan; B Pasaribu; T D Kusworo; S. Silviana; H S Kusuma; M. I. Khan; S. Haddout; J C C Casila; H. Harianingsih; W O Choo; M A Iqbal (International Journal of Environmental Science and Technology, 2025)

Retraction Note: Development and evaluation of methotrexate-loaded nanoemulsion formulation for topical treatment of psoriasis - Sheikh Abdur Rashid; Faiza Naseem; Pervaiz Akhtar Shah; Hamna Batool Hashmi; Mudassar Mazher; Mohammad S. Mubarak; Javad Sharifi-Rad; Muhammad Badar (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Development and evaluation of methotrexate-loaded nanoemulsion formulation for topical treatment of psoriasis - Sheikh Abdur Rashid; Faiza Naseem; Pervaiz Akhtar Shah; Hamna Batool Hashmi; Mudassar Mazher; Mohammad S. Mubarak; Javad Sharifi-Rad; Muhammad Badar (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Green Synthesis of Zinc Oxide Nanoparticles, Characterization and Its Applications in Inducing Disease Resistance Against Spot Blotch Disease in Wheat by Enhancing Its Physiological and Biochemical Parameters - Asif Kamal; Jinguang Yang; Momal Batool; Ulfat Ara; Waseem Ahmed Khattak; Driss Touhami; Reem M. Aljowaie; Mohamed S. Elshikh (Journal of Crop Health, 2025)

Foliar epidermal micromorphology: a contribution to the taxonomy of family Oleaceae - Tajalla Batool; Muhammad Zafar; Mohamed S. Elshikh; Abd El-Zaher M. A. Mustafa; Mushtaq Ahmad; Trobjon Makhkamov; Sokhib Islamov; Dilnoza Sotiboldiyeva; Akramjon Yuldashev; Mozaniel Santana De Oliveira; Salman Majeed; Inomjon Bakhramov; et al. (Genetic Resources and Crop Evolution, 2025)

Effective synergism of Moringa oleifera with antibiotics, body growth, and decoction replacement - Qandeel Ashraf; Amjad Islam Aqib; Hamid Majeed; Shahbaz Ul Haq; Muhammad Farrukh Nisar; Muhammad Usman; Afshan Muneer; Saba Batool; Farid S. Ataya (South African Journal of Botany, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Novel green sorbent Aerva Javanica for dyes remediation from aqueous media and future prediction through QSPR modeling - H. Y. Gondal; F. Batool; S. Iqbal; J. Akbar; S. Noreen; M. Mustaqeem; M. F. ur Rehman; M. Imtiaz; R. Qadir (International Journal of Environmental Science and Technology, 2024)

Correction: Cobalt Uptake by Food Plants and Accumulation in Municipal Solid Waste Materials Compost-amended Soil: Public Health Implications - Zafar Iqbal Khan; Asma Ashfaq; Kafeel Ahmad; Aima Iram Batool; Mehwish Aslam; Tasneem Ahmad; Naunain Mehmood; Ijaz Rasool Noorka; Abdel-Rhman Z. Gaafar; Mohamed S. Elshikh; Syed Sikandar Habib; Riaz Khan; et al. (Biological Trace Element Research, 2024)

Cobalt Uptake by Food Plants and Accumulation in Municipal Solid Waste Materials Compost-amended Soil: Public Health Implications - Zafar Iqbal Khan; Asma Ashfaq; Kafeel Ahmad; Aima Iram Batool; Mehwish Aslam; Tasneem Ahmad; Naunain Mehmood; Ijaz Rasool Noorka; Abdel-Rhman Z. Gaafar; Mohamed S. Elshikh; Syed Sikandar Habib; Riaz Khan; et al. (Biological Trace Element Research, 2024)

Comparison between carbon nanotubes and molybdenum trioxide nanoparticles embedded in polymeric membrane for environmental remediation - A. Abbass; S. Hassan; Z. Imran; S. S Batool; M. Ahmed; A. I Ahmad; D. Mazhar; S. Zaman (International Journal of Environmental Science and Technology, 2024)

Enhancement of shelf-life of food items via immobilized enzyme nanoparticles on varied supports. A sustainable approach towards food safety and sustainability - Sumaira Shouket; Shazia khurshid; Jahangir Khan; Razia Batool; Abid Sarwar; Tariq Aziz; Majid Alhomrani; Abdulhakeem S. Alamri; Manal Y. Sameeh; Faten Zubair Filimban (Food Research International, 2023)

Insect-facilitated propagation of mycotoxic fungi in grain storages: association of Sitotroga cerealella Olivier with Aspergillus flavus link - A. A. Khan; U. Umar; S. Ejaz; H. Riaz; M. Batool; T. Chen; F. Ahmad; Q. Saeed (International Journal of Environmental Science and Technology, 2023)

Trehalose: a promising osmo-protectant against salinity stress—physiological and molecular mechanisms and future prospective - Muhammad Nawaz; Muhammad Umair Hassan; Muhammad Umer Chattha; Athar Mahmood; Adnan Noor Shah; Mohamed Hashem; Saad Alamri; Maria Batool; Adnan Rasheed; Maryam A. Thabit; Haifa A. S. Alhaithloul; Sameer H. Qari (Molecular Biology Reports, 2022)

Assessment of heavy metal contamination and its sources in urban soils of district Hyderabad, Pakistan using GIS and multivariate analysis - R. K. Bux; S. I. Haider; M. Batool; A. R. Solangi; Z. Shah; H. Karimi-Maleh; F. Sen (International Journal of Environmental Science and Technology, 2022)

Copper chromite/graphene oxide nanocomposite for capacitive energy storage and electrochemical applications - R. Shafique; M. Rani; A. Mahmood; S. Khan; N. K. Janjua; M. Sattar; K. Batool; T. Yaqoob (International Journal of Environmental Science and Technology, 2022)

Integrated usage of synthetic and bio-fertilizers: an environment friendly approach to improve the productivity of sorghum - S. Akhtar; S. Bashir; S. Khan; J. Iqbal; A. B. Gulshan; S. Irshad; S. Batool; N. Ahmad; M. S. Rizwan (Cereal Research Communications, 2020)

Screening of maize hybrids against salt stress under hydroponic culture - M. M. Maqbool; A. Wahid; A. Ali; S. Khan; S. Irshad; S. Batool (Cereal Research Communications, 2020)

Butyrylcholinesterase in Substance Abuse: An Overview - S. M. Nurulain; A. Adem; S. Munir; R. Habib; S. Awan; F. Anwar; S. Batool (Neurophysiology, 2020)

Green is clean: the role of ICT in resource management - Rubeena Batool; Arshian Sharif; Talat Islam; Khalid Zaman; Alaa Mohamd Shoukry; Mohamed A. Sharkawy; Showkat Gani; Alamzeb Aamir; Sanil S. Hishan (Environmental Science and Pollution Research, 2019)

Molecular epidemiology of bovine anaplasmosis in Khyber Pakhtunkhwa, Pakistan - Shahid Hussain Farooqi; Muhammad Ijaz; Muhammad Imran Rashid; H. Nabi; S. Islam; Amjad Islam Aqib; Kashif Hussain; Amjad Khan; Syeda Nayab Batool Rizvi; Shakeel Mahmood; Khalid Mehmood; Hui Zhang (Tropical Animal Health and Production, 2018)

Efficacy of N-Acetylserotonin and Melatonin in the EAE Model of Multiple Sclerosis - Jie Wen; Prasanth S. Ariyannur; Rachel Ribeiro; Mikiei Tanaka; John R. Moffett; Batool F. Kirmani; Aryan M.A. Namboodiri; Yumin Zhang (Journal of Neuroimmune Pharmacology, 2016)

Comparison of different phases of bismuth silicate nanofibers for photodegradation of organic dyes - S. S. Batool; S. Hassan; Z. Imran; K. Rasool; M. Ahmad; M. A. Rafiq (International Journal of Environmental Science and Technology, 2016)

Study on cellular changes and potential endotrophy of wheat roots due to colonization of Chromium reducing bacteria - R. Batool; K. Yrjälä; S. Hasnain (International Journal of Environmental Science and Technology, 2015)

Microbial transformation of oleanolic acid by Fusarium lini and α -glucosidase inhibitory activity of its transformed products - M. Iqbal Choudhary; Iffat Batool; Shamsun Nahar Khan; Nighat Sultana; S. Adnan Ali Shah; Atta-Ur-Rahman (Natural Product Research, 2008)

Preliminary assessment of plant community structure and arbuscular mycorrhizas in rangeland habitats of Cholistan desert, Pakistan - M. S. Chaudhry; Z. Batool; A. G. Khan (Mycorrhiza, 2005)